Respuesta :
If you would like to solve the equation (a - c) / (x - a) = m for x, you can do this using the following steps:
(a - c) / (x - a) = m
a - c = m * (x - a)
a - c = mx - ma
mx = a - c + ma
x = (a - c + ma) / m
x = a/m - c/m + a
The correct result would be x = a/m - c/m + a.
(a - c) / (x - a) = m
a - c = m * (x - a)
a - c = mx - ma
mx = a - c + ma
x = (a - c + ma) / m
x = a/m - c/m + a
The correct result would be x = a/m - c/m + a.
We are given with the equation (a-c)/(x-a) = m. In this case, to isolate x, we can use the division, multiplication, addition adn subtraction properties. In this case, Divide the whole equation by m, to give, (a-c)/(x-a)/m = 1. Then multiply by (x-a). Then to isolate x, add a. this results to
x = [(a-c)/m]
x = [(a-c)/m]